Reliability, validity, and ability to identify fall status of the Balance Evaluation Systems Test, Mini–Balance Evaluation Systems Test, and Brief–Balance Evaluation systems est in Older people Living in the Community - Marques, Alda (2016)
To assess the reliability, validity, and ability to identify fall status of the Balance Evaluation Systems Test (BESTest), Mini-BESTest, and Brief-BESTest, compared with the Berg Balance Scale (BBS), in older people living in the community. Design Cross-sectional. Setting Community centers. Participants Older adults (N=122; mean age ± SD, 76±9y). Interventions Not applicable. Main Outcome Measures Participants reported on falls history in the preceding year and completed the Activities-Specific Balance Confidence (ABC) Scale. The BBS, BESTest, and the Five Times Sit-To-Stand Test were administered. Interrater (2 physiotherapists) and test-retest relative (48–72h) and absolute reliabilities were explored with the intraclass correlation coefficient (ICC) equation (2,1) and the Bland and Altman method. Minimal detectable changes at the 95% confidence level (MDC95) were established. Validity was assessed by correlating the balance tests with each other and with the ABC Scale (Spearman correlation coefficients–ρ). Receiver operating characteristics assessed the ability of each balance test to differentiate between people with and without a history of falls. Results All balance tests presented good to excellent interrater (ICC=.71–.93) and test-retest (ICC=.50–.82) relative reliability, with no evidence of bias. MDC95 values were 4.6, 9, 3.8, and 4.1 points for the BBS, BESTest, Mini-BESTest, and Brief-BESTest, respectively. All tests were significantly correlated with each other (ρ=.83–.96) and with the ABC Scale (ρ=.46–.61). Acceptable ability to identify fall status (areas under the curve,.71–.78) was found for all tests. Cutoff points were 48.5, 82, 19.5, and 12.5 points for the BBS, BESTest, Mini-BESTest, and Brief-BESTest, respectively. Conclusions All balance tests are reliable, valid, and able to identify fall status in older people living in the community. Therefore, the choice of which test to use will depend on the level of balance impairment, purpose, and time availability.